PENGOLAHAN LIMBAH CAIR PERIKANAN MENGGUNAKAN KONSORSIUMMIKROBA INDIGENOUS PROTEOLITIK DAN LIPOLITIK - Devi Ambarwaty Oktavia; Djumali Mangunwidjaja; Singgih Wibowo; Titi Candra Sunarti; Mulyorini Rahayuningsih (AGROINTEK, 2012)
Fish processing industries produce liquid waste at different capacity in every level from production line. Because of less attention and knowledge, wastes become worse. The aim of this study was to discover potential microbial consortium that can degrade protein and fat of liquid waste from fish production processing. The consortiums formula were chosen from bacteria that  have the highest specific growth. Formulation A which degraded soluble protein than others. Formulation of B which degraded fat than others. All formulation had pH in range are 6 - 9. Liquid waste which outoclaved had degraded protein, soluble protein and pH parameters